An Analysis of the Effects of a Multi-Tiered Stock Market - Reilly, Frank K.; Drzycimski, Eugene F. (Journal of Financial and Quantitative Analysis, 1981)
Frank K. Reilly, Eugene F. Drzycimski, An Analysis of the Effects of a Multi-Tiered Stock Market, The Journal of Financial and Quantitative Analysis, Vol. 16, No. 4, Proceedings of 16th Annual Conference of the Western Finance Association, June 18-20, 1981, Jackson Hole, Wyoming (Nov., 1981), pp. 559-575